Case Study of the Role of Health Education in Raising Public Awareness of the Importance of Preventing Infectious Diseases - Yunita Kristina; Eni Efanti; Fauziah Botutihe; Ari Pebru Nurlaily; Putri Erlyn (CV. Get Press Indonesia, 2024)
One of the main factors leading to the high incidence of infectious diseases is the low knowledge and preventive behaviour among the community (Alodokter, 2018; Hellosehat Kemenkes, 2022). This study aims to examine the role of health education in increasing public awareness of the importance of infectious disease prevention, and to analyse the effectiveness of educational methods used in various health programmes. This research uses a case study method with a qualitative approach. Case studies were chosen because they allow researchers to explore in depth the phenomenon of the role of health education in increasing community awareness of the importance of preventing infectious diseases (Ismadi, 2023). The focus of this study was to holistically understand health education interventions in a particular community and their impact on behaviour change and community awareness From the results shown in Table 1, the attitudes of subjects I and II before being given health counselling related to infectious diseases were in the less category with a percentage of 60%. Table 2 shows that after being given health counselling to improve family attitudes in preventing infectious diseases in adolescents. Subject I where the pre-test results were 60% and post-test results were 90%. The importance of health education in preventive interventions, which has a tangible impact on behaviour change and reduced risk of disease transmission.